Design and Implementation of Interworking System for Device Interaction in a Virtual Reality Setting - Jang, Rae-Young; Bae, Jong-Hwan; Lee, Heung-Ryong; Bak, Seon-Hui (Journal of Digital Contents Society, 2019)
The virtual training system utilizing Augmented Reality(AR), Virtual Reality(VR) and Mixed Reality(MR) eliminates realistic limitations and enables a repeated experience of safe and efficient VR training. Considering the training system is usually designed for one individual and limited to a simple repetitive experience, there’s a restriction to develop as a mutually interactive training mechanism. In order for multiple users to interact with each other in the training, it is necessary to identify the objects through a head mounted display (HMD) and to have a middleware facilitating the interactions. This paper aims to design a system in which two individual users can simultaneously identify each other’s movements in the same training based on the related technology. KCI Citation Count: 3